Biosorption of heavy metals using Pleurotus Ostreatus fungal mycelium from mushroom farming waste / Prof. Sr. Ir. Dr. Suhaimi Abdul Talib … [et al.] - Abdul Talib, Suhaimi; Surif, Salmijah; Liew, Hong Hooi; Yong, Soon Kong (Research Management Institute (RMI), 2011)
Industrial wastewater containing heavy metals are hazardous, which pose a detrimental health implication to human and environment. Global industrialization development has increased the discharge of this dangerous industrial wastewater to surface water. It is of great concern nowadays due to its toxicity, non-biodegaradable and cumulative characteristics. Heavy metals, such as lead, cadmium, copper, nickel and mercury, are from metal plating, painting and metal finishing industries. The most commonly used method in heavy metals treatment for industrial wastewater is precipitation with caustic soda. However, this method generates a large amount of hydroxide sludge which need further disposal. In view of this, interest which focus on green sustainable biosorption process, has been intensified among researchers recently. Biosorption is a passive metabolic independent process involving physico-chemical binding of metal ions with biosorbent, which from nonliving biological materials. The biosorbent offers two major advantages, namely, renewable and cost effective. It is easily regenerated by using diluted acid for reuse and transformed from available large amount of bio-waste to wealth. Biosorbents from agricultural and industrial waste which are available in respective countries, such as Brazil, India, Pakistan, Iran, China and Turkey have been investigated. Fungal Pleurotus ostreatus (Chia-Chay et a/., 2011, Javaid et a/., 2011) and sawdust (Zakaria et a/., 2009) are promising biosorbents due to their high heavy metals removal efficiency if compared to other plant or bacteria derived biosorbents. To date, there is lack of information on biosorption of Pleurotus ostreatus Mushroom Spent-Substrate (PSMC) in wastewater heavy metals treatment. Generally, the PSMC is an agricultural waste of mushroom cultivation farm in Malaysia, which majorly consists of rubber tree sawdust and Pleurotus ostreatus mycelium. The disposal of PSMC is currently handled by open-burning or converted into low commercial value organic fertilizer in order to reduce cost for solid waste disposal. Studies on PSMC as a potential biosorbent for heavy metals treatment is yet to be explored. Meanwhile in biosorption study, the half saturation constant of biosorption evaluation is seemed hardly been carried out as a time saving approach for this alternative sustainable technology. Presently, little research is applying the Artificial Neural Networks (ANN) in biosorption study. Kardam and co-researchers (2010) reported that constructed ANN models were highly precise in predicting the single output variable. In fact, such single output ANN network has a limitation in simulation of biosorption operating system for prediction of effluent quality and the best time for elution of biosorbent under any operating conditions. This study is thus expected to make contribution to the knowledge of scale-up biosorption of heavy metals technology. This study focuses on biosorption characteristics of heavy metals biosorption from aqueous solution by deploying PSMC. The half saturation constant of heavy metals biosorption and the best operating parameters of initial pH, contact time and initial heavy metals concentration were optimized. Biosorption data were fitted to established isotherm, kinetic and thermodynamic models. Concurrently, mechanisms of heavy metals biosorption were studied. Application of biosorbent was evaluated in industrial wastewater. Furthermore, a constructed ANN modelling with two output in biosorption study is explored. This study is not only parallel with green sustainable technology for heavy metals treatment but also waste management.